Korelasi negatif kuat kadar prolaktin plasma yang rendah terhadap derajat keparahan melasma - Angela Sandi Tagaroi Rahasia; Anak Agung Gde Putra Wiraguna; Luh Made Mas Rusyati (DiscoverSys Inc., 2019)
Background: Melasma is a chronic cutaneous hypermelanosis in areas exposed to sunlight. Hormonal factors are known to influence melanogenesis processes such as prolactin as a neuroendocrine modulator in skin epithelial growth and immune system. This study aims to prove the inverse relationship between plasma prolactin levels and the severity of melasma.Methods: A cross-sectional study was carried out on 59 patients in the skin and genital olyclinic at Sanglah Hospital in Denpasar involving 46 subjects of melasma and 13 subjects who were not melasma who met the inclusion and exclusion criteria. Plasma prolactin levels were assessed by the Chemiluminescent microparticle immunoassay (CMIA) method. Data analysis was performed using SPSS ver. 23 software with a P-value <0.05 was considered statistically significant.Results: Plasma prolactin levels in patients with melasma were significantly lower than non-melasma patients (p <0.05). Patients with moderate and severe degrees of melasma had significantly lower plasma prolactin levels compared with mild degree of melasma (p <0.05). Low plasma prolactin levels can increase the likelihood of melasma by 4.79 times (PR 4.79; 95% CI = 0.94-24.27; p <0.05). Low plasma prolactin levels were significantly strong negative correlated with melasma severity (r = -0.820; p <0.05).Conclusion: There is a strong negative correlation of low plasma prolactin levels with the severity of melasma in patients with skin disorders at Sanglah General Hospital